Phenotypic delimitation supports a new rupicolous species of Cattleya (Orchidaceae: Laeliinae) from the Diamantina Plateau, Minas Gerais, Brazil - Menezes, Euler Da Luz Fernandes; Viotti, Julia; Giordani, Samuel Cunha Oliveira; Pinheiro, Rodrigo Almeida; Machado, Evandro Luiz Mendonça; Neves, Danilo Rafael Mesquita (Phytotaxa, 2026)
Cattleya ramosii sp. nov. is described here from the campo rupestre vegetation of the Diamantina Plateau, Minas Gerais State, Brazil. The new species is a small rupicolous taxon of Cattleya ser. Parviflorae that is morphologically close to C. haroldoi, C. porphyrascens, and C. vandenbergii. We compiled a multi-categorical dataset from cultivated specimens and quantified dissimilarity using coincidence frequency, followed by Ward clustering and Principal Coordinate Analysis, to validate phenotypic discontinuity among the four taxa. The analyses recovered four coherent clusters consistent with species boundaries, with floral characters most contributing to their separation. The species is currently known from a single locality, where it grows in rock fissures on cliffs; it flowers mainly in October–November. Given its limited distribution, the low number of individuals recorded, and evidence of anthropogenic fires affecting nearby outcrops, C. ramosii is provisionally assessed as Data Deficient (DD). An identification key and comparative notes are provided to facilitate recognition of the new taxon and its similar congeners.